The essence of the rule of law and the main directions of its building in Ukraine: theoretical and legal research - Kravchuk , Mykola (Actual problems of law (Aktual’ni problemi pravoznavstva), 2024)
This scientific article substantiates the importance of the rule of law in the creation of a state in Ukraine. The pluralist concept of the rule of law is revealed. Various approaches to the definition of the concept of "rule of law state" are outlined, its main features are highlighted. The following requirements for establishing the rule of law are considered in detail: the great importance of natural, inalienable and inalienable human rights and freedoms; the principle of the distribution of power, which provides for the existence of relatively independent and independent branches of power - legislative, executive, judicial, and the establishment of such relationships between them that would make it impossible to usurp all or most of the state power in the hands of one state body, and even more so in hands of one person; limitation of discretionary powers; the supremacy of the Constitution; the principle of legal certainty, which means the requirement of clarity of the grounds, goals and content of regulatory prescriptions, especially those addressed directly to citizens; the principle of proportionality regulates the relationship between the set goal and the means and methods of achieving it; the principle of legal security and protection of the citizen’s trust in his legal position; independence of the court and judges. An assessment of the level of construction of such a state in Ukraine has been carried out. The main directions of building a rule of law state have been established.